The God Of Small Things - Arundhati Roy
Compared favorably to the works of Faulkner and Dickens, Arundhati Roy$1 (Bs debut novel is a modern classic that has been read and loved worldwide. Equal parts powerful family saga, forbidden love story, and piercing political drama, it is the story of an affluent Indian family forever changed by one fateful day in 1969. The seven-year-old twins Estha and Rahel see their world shaken irrevokably by the arrival of their beautiful young cousin, Sophie. It is an event that will lead to an illicit liaison and tragedies accidental and intentional, exposing (3z(Bbig things [that] lurk unsaid(3y (Bin a country drifting dangerously toward unrest. Lush, lyrical, and unnerving, The God of Small Things is an award-winning landmark that started for its author an esteemed career of fiction and political commentary that continues unabated.s